ACTR-71. FULL ENROLLMENT RESULTS FROM THE PHASE 1/2, MULTICENTER, OPEN-LABEL STUDY OF MARIZOMIB (MRZ) ± BEVACIZUMAB (BEV) IN RECURRENT WHO GRADE IV MALIGNANT GLIOMA (GLIOBLASTOMA, RGBM). (6th November 2017) - Bota, Daniela; Desjardins, Annick; Mason, Warren; Kesari, Santosh; Magge, Rajiv; Winograd, Benjamin; Reich, Steven D; Levin, Nancy; Trikha, Mohit
Abstract: MRZ – an irreversible, brain-penetrant, pan-proteasome inhibitor with anti-glioma preclinical activity – was evaluated in BEV-naïve rGBM patients. METHODS: Phase 1 (P1) MRZ+BEV, 3 + 3 MRZ dose-escalation (N=6, 3, 3 at 0.55, 0.7, 0.8 mg/m2) followed by dose-expansion (N=24, 0.8 mg/m2). Phase 2 (P2) MRZ monotherapy (N=30, 0.8 mg/m2). Treatments (IV, 28-day (D) cycles): MRZ (10min infusion) D1, 8, 15; BEV (10 mg/kg) D1, 15. Tumor response (RANO criteria) every other cycle; MRZ and BEV PK, and proteasome inhibition in blood evaluated in P1. RESULTS: as of 14Apr2017: P1 mean age 55 yrs, 64% male, mean treatment duration 5.3 cycles, 1 patient active; P2 56 yrs, 57% male, 2.5 cycles, 6 patients active. One DLT (fatigue) in P1 at 0.55 mg/m2, no other DLTs. P1 treatment-related AEs (TRAEs Grade ≥3 in ≥2 patients): hypertension, headache, confusional state, fatigue, hallucination, proteinuria; three Grade 4 SAEs (appendicitis perforated, depressed level of consciousness, not-related; blindness, BEV-related), three Grade 5 SAEs (2 PD, not-related; intracranial hemorrhage, BEV-related). P2 TRAEs (Grade ≥3 in ≥2 patients): fatigue, hallucination, lethargy; one Grade 4 SAE (hallucination). P1 overall response (≥PR) 44% (16/36) including 1 CR, 15 PR; overall survival (OS) at 6/9/12 months (mos) 75/60/39%, median 9.4mos; OS 68/45/15% (median 7.2mos) in unmethylated MGMT (uMGMT, N=22), 78/78/67% (median not reached) in methylated MGMT (N=10). In P2: 1 PR, 6 SD; 4 patients (3 SD, 1 PR) ongoing at 5–10 cycles. P1 patients experiencing ≥1 CNS-related AEs (any grade: ataxia/balance disorder/dizziness/dysarthria/fall/gait disturbance/hallucination) have increased OS (83/74/45%, median 11.4mos, N=23) versus patients without these AEs (59/34/25%, median 6.3mos, N=13). CONCLUSIONS: MRZ monotherapy and MRZ+BEV active in rGBM overall and in uMGMT. Possible therapeutic improvement in patients experiencing CNS AEs will be explored in ongoing P2 MRZ+BEV extension allowing intra-patient MRZ dose-escalation if no CNS AE in first cycle (0.8 mg/m2).